Study of the grades of public high schools, general aptitude, and achievement tests in Madinah schools during the period from 1433-1434AH, (2012-2013) to 1439-1440AH, (2018-2019) and its projection for the next three years - Bukhari, Shukri Ahmed Khaja (Journal of Educational and Psychological Sciences, 2022)
The study aimed to study the grades of public high schools, general aptitude, and achievement tests in Madinah schools during the period from 1433-1434AH, (2012-2013) to 1439-1440AH, (2018-2019) and forecast for the next three years at the General Education Management in Madinah, and then develop prognostic mathematical models for the next three years. The researcher adopted the descriptive approach and extracted the texts’ grades of (88563) students for the general aptitude and achievement tests as well as high school grades from the Noor system. Thereafter, he studied the grades progression during the years from 1433-1434AH, (2012-2013) until 1439-1440AH, (2018-2019). Then, he created mathematical models to predict for the next three years in order to help the decision-maker in the General Education Management in Madinah know what the situation will look like in the coming years to take appropriate developmental measures. The most important findings of the study include that the appearance of a stable and slightly high grade in the public high schools in the Management indicates the care and concern of the General Education Management in Madinah for the high school grades. The findings also reveal an unsteady and simultaneous fluctuating progression in the grades of the general aptitude and achievement tests, which indicates the lack of sufficient attention given to them and the need for the General Education Management in Madinah to pay more attention to them. The researcher recommends that the Education Management in Madinah should urge supervisory offices, educational leaders, and teachers to work hard to develop educational work in schools to include the development of general and specific skills and abilities in basic scientific subjects in a way that will reflect on students’ performance in national and international scientific and educational tests.
Keywords: Evaluation; Mathematical model; Education Department